La Commedia dell’Arte. Un fenomeno europeo - Siro Ferrone (Drammaturgia, 2020)
The expression ‘Commedia dell’Arte’ refers to a Europe-wide theatrical phenomenon based on the activity of professionals gifted with many abilities and willing to travel. The invenzione viaggiante is one of the hallmarks of the comics spectacle: through the dimension of journey, performers acquire expressive techniques and a mnemonic repertoire of compositions, images, sounds, and songs, which enables them to overcome geographic and linguistic boundaries and to be appreciated by different audiences. The essay aims to highlight some key aspects of the Commedia dell’Arte in Italy and Europe, also by focusing the experience of Ludovico Ottavio Burnacini, an exceptional ‘migrant’ in Vienna.